We Are the State! : Barrio Activism in Venezuela's Bolivarian Revolution - Valencia, Cristobal (Book collections on Project MUSE., 2015)
"This book is about Hugo Chávez's supporters: the Chavistas, the life-blood of Venezuela's Bolivarian Revolution. "We are the State!" examines the race, class, and gender subjective experiences of the Chavistas in everyday processes of state formation and in establishing democracy"--Provided by publisher.